Efektivitas Model Project Based Learning Terhadap Keterampilan Membaca Pada Siswa Kelas IX SMPN 40 Makassar - Rahman, Fatur; Sakaria, Sakaria (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the effectiveness of the use of the project-based learning model on the reading learning outcomes of Class IX students at SMPN 40 Makassar. This research is a type of quantitative research with an experimental research design. The sample in this study amounted to 32 students. The data collection technique in this study was a multiple choice test. The collected data were analyzed with descriptive statistics and inferential statistics. The results of data analysis showed that: (1) the reading ability before using the Project Based Learning model was categorised as poor with an average score of 50.93, (2) the reading ability after using the Project Based Learning model of class IX students of SMPI 40 Makassar was categorised as sufficient with an average score of 63.43 by obtaining an increase of 12.5, and (3) the results of hypothesis testing from the results of the analysis of students' pretest and posttest data showed that the results of t count ≥ t table, namely 9.153 > 2.042, it can be concluded that H1 is accepted, namely the Project Based Learning model is effectively applied in reading learning to students of class IX SMPI 40 Makassar.